Between LSE and Cambridge: Accounting for Ronald Coase's fascination with Alfred Marshall - Steven G. Medema (Duke University, Center for the History of Political Economy (CHOPE), 2019)
We examine Coase's biographical work on Marshall and his discussions of Marshall's economics for clues as to the sources of Coase's affinity for Marshall. And as we shall see, the evidence suggests explanations that are at once personal and professional.
Keywords: 330